Consumo de antihipertensivos de mayor prescripción en un establecimiento farmacéutico - Piura, Enero - Diciembre 2016 - Poma Avila, Oliver Pierre (2019)
The present report is a cross-sectional, retrospective and descriptive study whose objective was to determine the characteristics of antihypertensive drug consumption in a pharmaceutical establishment in Piura, province of Piura, department of Piura, in which the pre-professional practices were carried out. , during the aforementioned period. The determination of the study is based on the data provided by the inkaventas system, which allows to observe and obtain information of the different brands with greater degree of dispensation and commercialization that exist in the Peruvian market. The methodology used was through the number of daily doses defined per thousand inhabitants and day (DHD). Data from the dispensed units of enalapril, captopril, losartan, hydrochlorothiazide and their commercial equivalents, and their commercial equivalents (Hipersol, Melatil, Sarlotas, Diurace) during the January - December 2016 period, resulting in the highest consumption month, were considered. in the month of August with S /. 1603 being enalapril the one with the highest annual consumption with 3174 units. The highest consumption of captopril (number of DDD / 1000 inhabitants / day = 5.98) stands out with respect to all other antihypertensive drugs. December is the month with the highest DHD number